Far Out on the Yield Curve - Annika Alexius (Uppsala University, Department of Economics, 2004)
Data on short investments in Swedish long-term bonds as the bonds mature contains unusually rich information about the relationship between duration and the first and second moments of bond returns. We identify three different channels through which duration affects bond returns. The liquidity preference hypothesis yields a direct link between duration and returns, which however disappears once indirect effects through the variance of returns and the price of risk are taken into account. The risk premia obtained from a multivariate GARCH-M model extended to allow the variance to depend on duration are of the same size as observed excess returns. Finally, duration appears to affect the relationship between bond returns and the risk free interest rate. One additional year of duration implies that the beta-coeffcient increases by 0.66.
Keywords: C12; E43; 330; Bond returns; duration; multivariate GARCH; Zinsstruktur; ARCH-Modell